2011
DOI: 10.3109/14767058.2010.531325
|View full text |Cite
|
Sign up to set email alerts
|

Acute fatty liver of pregnancy: diagnosis, treatment, and outcome based on 35 consecutive cases

Abstract: We found a typical 'AFLP-Triad' in women with AFLP. First (symptoms): nausea/vomiting, jaundice, epigastric pain; second (laboratory): results indicated renal dysfunction, coagulopathy, liver function abnormalities, low glycemia, and third (complications): renal failure, coagulopathy, ascites, and encephalopathy. We recommended that patients with this triad received evaluation to rule out the diagnosis of AFLP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
46
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 12 publications
2
46
1
2
Order By: Relevance
“…The outcome is often lethal, with a high stillbirth and maternal death rate of about 12 % each [188,189].…”
Section: Clinical Relevancementioning
confidence: 99%
“…The outcome is often lethal, with a high stillbirth and maternal death rate of about 12 % each [188,189].…”
Section: Clinical Relevancementioning
confidence: 99%
“…(10) Simultaneously, neonatal mortality rate has also decreased, which is in the range of 7% to 66%. (3,11) Previous clinical studies on AFLP, largely based on a few patients due to its low prevalence, have found large variations in results vis-à-vis its epidemiology, (2)(3)(4)(5)(6) symptoms, (12) complications (12) and outcomes. (3,10,11,13) For instance, Cheng et al (14) found that, besides aetiology, other clinical characteristics of pregnancy (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Existing evidence shows that the aetiology of AFLP may involve oxidative stress on the liver, increased levels of serum arachidonic acid and abnormalities in the intramitochondrial processes of fatty acid oxidation, such as long-chain 3-hydroxyacyl coenzyme A dehydrogenase deficiencies caused by G1528C mutation. (1,3) Estimated incidence reported for AFLP ranges approximately from 1 in 7,000 deliveries to 1 in 20,000 pregnancies, (2)(3)(4)(5)(6) suggesting a low prevalence among pregnant women.…”
Section: Introductionmentioning
confidence: 99%
“…Rather than an indolent chronic disease, AFLP is a devastating condition that can rapidly progress to fulminant hepatic failure with associated coagulopathy or hepatic encephalopathy. In this scenario, the lives of two individuals (i.e., mother and infant) are inevitably jeopardized (3, 4). …”
mentioning
confidence: 99%
“…Since its initial description in 1940, AFLP has been considered an obstetric emergency that can lead to multiple organ failure in a short time unless it is diagnosed promptly (3, 4). The diagnosis of AFLP is based on the Swansea criteria, which represent a constellation of signs and symptoms, along with abnormal lab tests such as elevated aminotransferases (10).…”
mentioning
confidence: 99%